Validitas Perangkat Pembelajaran Etnoekologi Masyarakat Suku Sasak Kawasan Taman Nasional Gunung Rinjani - Setiana Dwi Utami; Ismail Efendi; Ika Nurani Dewi; Agus Ramdani; Immy Suci Rohyani (Postgraduate, University of Mataram, 2019)
Abstract. The Government of the Republic of Indonesia establishes the competence of college graduates to master the science field and being able to apply it in daily life, one of them is to connect the learning materials with the environment and cultural surroundings through Ethnoecology. The disclosure of ideas by local communities through ethnoecological learning can strengthen the nature of meaningful learning and encourage the students' positive attitude to solve the problems wisdom. The Ethnoecology form of the Sasak Tribe in Mount Rinjani National Park Area is integrated into learning in the form of local knowledge, local intelligence, and local policies. The Ethnoecology Learning development method consisting of RPS, SAP, MFIS, and assessment instruments refer to the ADDIE development model. The Ethnoecology learning developed in this study needs to be validated by practitioners and experts. Based on the feasibility validation result of the ethnoecology learning tool belongs to the category of logical and religious validity, so that it can be used as a support in the implementation of ethnoecology learning. A good learning tool will create a quality learning process. Keywords: Validity; Learning tools; Ethnoecology